PENANGANAN MAMALIA LAUT TERDAMPAR LUMBA-LUMBA SPOTTED DOLPIN (Stenella attenuata) DI UJONG BATEE - Melinda, Sri; Kusumawati, Ika; Rahma, Endah Anisa (Jurnal Abdi Insani, 2024)
This activity is a special activity that uses market research methods in its application, identification using the Rapid Assessment method refers to the Fahmi & White (2006) method. This activity was carried out at the UPTD Water Area Management, Aceh Maritime Affairs and Fisheries Service on September 20 and 21. In this activity the tools used were a digital camera used to record the activity, a field guide "Economically Important Sharks and Rays in Indonesia" to identify dolphins caught in Prikanan Aceh and a 50 m camera to compare dolphin sizes. a scale is used. Get typed documents. Data collection takes place from the start of the activity at TPI (06:00 WITA) until the end (10:00 WITA) and in the afternoon (15:00 WITA depending on the weather and season). Data collection began with identifying the type of dolphin caught referring to the field guide "Economically Important Sharks and Rays in Indonesia", after which the dolphin population was calculated based on type and comparison. digital documents. The camera and interview were briefly filmed with a fisherman who caught the dolphin above where the dolphin was caught. Since this is a protected species, care and ownership rules must be followed for the good of the animal. and dolphin care is considered essential and requires regulatory oversight to prevent cruelty to animals.